The Impact of Digital Marketing via TikTok Shop on Generation Z’s Purchase Decisions - Hodijah, Cucu; Rahmani, Shinta; Abdillah, Fatimah (SAFE-Network, 2025)
This study aims to analyze the impact of digital marketing through TikTok Shop on Generation Z’s purchase decisions. As a rapidly growing social media platform, TikTok has become one of the most effective e-commerce channels, with TikTok Shop allowing users to purchase products directly through the videos they watch. Generation Z, as a group highly connected with technology, is greatly influenced by digital marketing presented on social media platforms. This study uses a quantitative approach with a survey as the data collection method. A total of 210 respondents who are active TikTok users and have made purchases through TikTok Shop participated in this study. The data was analyzed using descriptive statistical analysis and hypothesis testing with Structural Equation Modeling (SEM). The results show that brand awareness, purchase intention, influencer impact, and user engagement significantly affect Generation Z’s purchase decisions through TikTok Shop. This study provides valuable insights for marketers to design more effective marketing strategies on TikTok, leveraging influencer impact and the platform's interactivity to boost conversion rates. Overall, the findings emphasize that TikTok Shop is a highly potential marketing tool for reaching young consumers and influencing their purchasing decisions.